MENYELISIK KEPATUHAN PAJAK PELAKU UMKM DI WILAYAH JABODETABEK DARI PERSPEKTIF CREATIVE TAX MORALE - Maritsa Agasta Putri; Arief Budi Wardana (Bina Ekonomi, 2021)
The reason why people pay taxes is still questionable in various tax compliance literatures. Tax morale is believed to be one of the factors that motivate people to pay taxes. This study aims to analyze the determinants of tax morale in influencing the level of tax compliance. Using a questionnaire survey and a multivariate test procedure, this study shows that tax morale and tax compliance can be increased by decreasing the level of corruption, improving the efficiency of government spending, increasing fairness in the taxation system, reducing tax rates, and addressing financial constraints. In addition, this study also proves that there is significant difference on tax morale between age category, while other socio-demographic and socio-economic categories have no significant difference. The results of this study are expected to add references in the tax compliance literature and become a consideration for tax authorities in improving tax compliance.  Keywords: tax morale, tax compliance, MSME.